(untitled) - Mureta, Chad (New Jersey, 2012)
The book caters to many platforms including iPhone, iPad, Android, and BlackBerry.This book includes real-world examples to inspire those who are looking to cash in on the App gold rush.
Keywords: Application software,Application software,Mobile computing,Phần mềm ứng dụng,Phần mềm ứng dụng,Điện toán đi động; Development,Marketing,Computer programs,Phát triển,Thị trường,Chương trình máy tính